Remembering Komagata Maru : Official Reports and Contemporary Accounts - Bhattacharyya, Ananda (Brill | Manohar Publishers & Distributors, 2017)
More than a hundred years ago on 27 September 1914, a bunch of weary Indians reached Calcutta on a Japanese steamship called the Komagata Maru from Vancouver, Canada. This was the 'bloody' climax of one of the most fascinating episodes in the Indian national movement that continues to inspire popular culture and scholars even today. The present compilation not only gives a complete profile of the Komagata Maru incident but throws light on the Descriptive Roll of Sikhs and Punjabis arrested in connection with the event. The saga of the Komagata Maru is a significant reminder of the character of the criminal exploitation which the colonizers generally inflicted on the people they colonized. The notion of civilizational superiority of the Whites was intrinsic to Imperialism. The commemoration of Komagata Maru is an occasion to explore and investigate how the ruling groups come to imagine and construct 'Others' and 'Undesirables'. Viewing the Komagata Maru project as a 'deliberate plot to foment sedition' pointed to another kind of argument, widely contrary to the perception and objective of the passengers and Baba Gurdit Singh. Over the years the tragic journey of Komagata Maru has inspired South Asian poets and playwrights, historians and journalists to reconstruct and memorialize the event from multiple perspectives. This volume is an attempt to situate the whole event in its historical perspective.